Desenvolvimento de sistema construtivo e estrutural modular em aço para edificações para fins didáticos - Penazzi, Maria Emilia (Universidade Federal de São Carlos, 2015)
In the context of Construction, the constructive structural system is responsable for considerable parcel of the construction performance after its occupation. First, this research uses a theoretical boarding within a bibliographical revision about concepts of industrialized construction, approaching the current technician scene in Brazil, and confronting some of the main industrialized technologies available today in the segment of construction. Then, it is tried to demonstrated the technique viability of constructive and structural steel system through the development of a module that could be adjust to diferent archetypes of constructions. Such a way, it was opted to the choice of an existing building in the Federal University of São Carlos (UFSCar), called building of theoretical class rooms 7 (AT7), adapting its educational demand into a system modular in steel. For such boarding,the elaboration of solutions techniques, in a flexible and adaptable way to the initial projetual conception was necessary, contemplating not only space geometry in respect to its structure, but also considering closings systems, installations and logistic, inside industrialized construction thematic. As result, a viable technically modulation was elaborated, considering dimensional, structural and logistic points, so it could be applied or adjusted according to some situations of project, inside constructive and structural types boarded in this study. In this manner, the research presents practical character, therefore it is motivated by the necessity of approaching relative real problems to the projetual conception, supplying and fomenting techniques choices about industrialized systems, cooperating in the spreading of the concept of Industrialization in the technician scene.
Guidance Development for Housing Design for Educational Purposes using the Steel Modular Building System
Keywords: Construção civil; Sistema modular em aço; Industrialização da construção; Racionalização; Steel Modular System; Industrialization of construction; Rationalization; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL